Early‐onset thrombocytopenia in near‐term and term infants with perinatal asphyxia. Issue 4 (29th October 2013) - Boutaybi, N.; Steggerda, S. J.; Smits‐Wintjens, V. E. H. J.; van Zwet, E. W.; Walther, F. J.; Lopriore, E.
<x xml:space="preserve">Abstract</x> Background Neonates after perinatal asphyxia are at increased risk of thrombocytopenia. The correlation between perinatal asphyxia and the risk and severity of early‐onset thrombocytopenia is not well known. Objective To estimate the incidence, severity and risk factors for early‐onset thrombocytopenia in neonates after perinatal asphyxia. Methods We included all newborns (gestational age ≥ 36 weeks) admitted to our neonatal nursery due to perinatal asphyxia in this retrospective study. We collected platelet counts that were obtained within the first 48 h of life to estimate the incidence and severity of early‐onset thrombocytopenia. Results A total number of 171 neonates with perinatal asphyxia were included in the study. The incidence of early‐onset thrombocytopenia (platelet count < 150 × 109/l) was 51% (87/171). Several factors were associated with increased risk of early‐onset thrombocytopenia, including prolonged prothrombin time (PT) [odds ratio (OR) 1·18, 95% confidence interval (CI) 1·08–1·30, P < 0·01], prolonged activated partial thromboplastin time (APTT) (OR 1·07, 95% CI 1·03–1·11, P < 0·01), low Apgar score at 10 min (OR 1·25, 95% CI 1·08–1·45, P < 0·01) and high serum lactate (OR 1·12, 95% CI 1·06–1·19, P < 0·01). After multiple logistic regression analysis, we found an independent association between early‐onset thrombocytopenia and prolonged PT (OR 1·15, 95% CI 1·00–1·33, P = 0·045) and higher lactate level (OR 1·15, 95% CI 1·03–1·28, P = 0·01). Conclusions Early‐onset thrombocytopenia occurs frequently in neonates after perinatal asphyxia and is independently associated with PT and lactate level.